Thermal unfolding and conformational stability of the recombinant domain II of glutamate dehydrogenase from the hyperthermophile Thermotoga maritima. - Consalvi, V; Chiaraluce, R; Giangiacomo, L; Scandurra, R; Christova, P; Karshikoff, A; Knapp, S; Ladenstein, R (2000)
Domain II (residues 189-338, M(r) = 16 222) of glutamate dehydrogenase from the hyperthermophilic bacterium Thermotoga maritima was used as a model system to study reversible unfolding thermodynamics of this hyperthermostable enzyme. The protein was produced in large quantities in E.COLI: using a T7 expression system. It was shown that the recombinant domain is monomeric in solution and that it comprises secondary structural elements similar to those observed in the crystal structure of the hexameric enzyme. The recombinant domain is thermostable and undergoes reversible and cooperative thermal unfolding in the pH range 5.90-8.00 with melting temperatures between 75.1 and 68.0 degrees C. Thermal unfolding of the protein was studied using differential scanning calorimetry and circular dichroism spectroscopy. Both methods yielded comparable values. The analysis revealed an unfolding enthalpy at 70 degrees C of 70.2 +/- 4.0 kcal/mol and a DeltaC(p) value of 1.4 +/- 0.3 kcal/mol K. Chemical unfolding of the recombinant domain resulted in m values of 3.36 +/- 0.10 kcal/mol M for unfolding in guanidinium chloride and 1.46 +/- 0.04 kcal/mol M in urea. The thermodynamic parameters for thermal and chemical unfolding equilibria indicate that domain II from T.MARITIMA: glutamate dehydrogenase is a thermostable protein with a DeltaG(max) of 3.70 kcal/mol. However, the thermal and chemical stabilities of the domain are lower than those of the hexameric protein, indicating that interdomain interactions must play a significant role in the stabilization of T. MARITIMA: domain II glutamate dehydrogenase.